Search for the Anomalous tqγ and tqH Couplings in γp Collision at the LHC - B. Şahin (Advances in High Energy Physics)
We have investigated the constraints on the anomalous tqγ and tqH  (q=u,c) couplings through the photoproduction processes pp→pγp→ptγX→pbl+νlγX and pp→pγp→ptHX→pbl+νlbb-X at the LHC. We have obtained 95% confidence level bounds on the anomalous couplings by considering various values of detector acceptances and integrated luminosities. Improved constraints on the tqγ coupling have been obtained compared to current bounds.